Invivo Effect Analysis of Rhodomyrtus tomentosa Leaf Ethanol Extract Against Escherichia coli - Doris Noviani; Adisty Dwi Treasa; Ade Zakiya Tasman Munaf; Sri Winarsih; Dwi Yuni Nur Hidayati; Mukhamad Nooryanto; Sutrisno Sutrisno (Medical Laboratory Technology Journal, 2021)
Puerperium infection contributed 11 percent of 48.17 percent of maternal mortality during the puerperium period; one of the causes of increased risk of puerperium infection was bacteria Gram-negative Escherichia coli. Puerperium infection occurred because bacteria enter through the vagina, wounds on the insertion of the placenta, and other parts spread to blood throughout the body and damage the spleen, liver, and uterus. This research aimed to determine the effect of Rhodomyrtus tomentosa leaves ethanol extract (Rtl-EE) as an antibacterial on the spleen, liver, and uterus of Escherichia coli -induced puerperal infection model mice. Mice in the postnatal treatment group were induced by Escherichia coli bacteria intravaginally and given different doses of ethanol extract of Rhodomyrtus tomentosa leaves. Examination of bacterial colonies growth used pour plate method with EMBA media. The research results showed that the administration of Rtl-EE decreased the growth of bacterial colonies respectively in the liver 1280, 924, 330 CFU/mL; the uterus 1806, 1180, 874 CFU/mL; and the spleen 712, 112, 774 CFU/mL. Colony growth started to decrease at dose 1 of Rtl-EE (100mg/kg BW) of mice model of Escherichia coli -induced puerperal infection. Rhodomyrtus tomentosa leaves contain active compounds - phenols, flavonoids, saponins, tannins, alkaloids, and triterpenoids as antibacterial. Rtl-EE had an antibacterial effect by reducing the number of bacteria on the spleen, liver, and uterus of Escherichia coli -induced puerperal infection model mice. Further research needs to conduct to examine the toxic dose of Rhodomyrtus tomentosa leaves against Escherichia coli bacteria.